Does the quality of an embryo differ between long down-regulated and antagonist cycles among age and cycle day 3 FSH-matched women undergoing ART? - (:unkn) unknown (My University, 2015)
Amaç: Gonadotropin salgılayıcı hormon (GnRH) antagonistlerinin kullanıldığı sikluslarda agonist sikluslarına göre daha düşük gebelik oranları bildirilmiştir. GnRH agonist sikluslarında anlamlı olmayan %3,3 lük bir gebelik oranında artış vardır. Yaş ve üçüncü gün FSH değerleri eşleştirilmiş kadınlarda kısa ve uzun yardımcı üreme teknikleri (YÜT) sikluslarında embriyo gelişiminde farkın olup olmadığının araştırılması amaçlanmıştır. Hastalar ve Yöntem: Universiteye bağlı hastanenin YÜT merkezine başvuran 193 kadında retrospektif kohort analizi yapıldı. Yaş ve siklusun 3. günü serum folikül stimulan hormon (FSH) değeri benzer olan kısa ve uzun protokol ile klasik in vitro fertilizasyon (IVF) veya intrasitoplazmik sperm enjeksiyonu (ICSI) uygulanan hastalar dahil edildi. Group A, uzun GnRH analog protokolu, group B, ise kısa GnRh antagonist protokolü ile YÜT tedavisi aldı. Klinik ve devam eden gebelik oranları karşılaştırıldı. Üçüncü gün embriyo skorları gruplar arası karşılaştırıldı. Bulgular: Her iki grupta toplanan ve insemine edilen yumurta sayısı ve ortalama embriyo skorları benzer olmasına rağmen klinik ve devam eden gebelik oranları grup Ada grup Bye göre daha yüksekti. Sıfır fragmentasyon ve 8-10 blastomer olan 3. gün embriyo yüzdesi gruplar arası benzer idi. Sonuç: Uzun protokol YÜT tedavilerinde, kısa protokolde elde edilenlere benzer oranda 8-10 blastomerli, simetrik ve sıfır fragmentasyonlu 3. gün embriyoları görülmektedir.

Objective: Lower pregnancy rates have been reported in gonadotropin releasing hormone (GnRH) antagonist cycles in comparison to those with agonist cycles. A non-significant difference of 3.3% in the pregnancy rate per cycle in favour of GnRH agonists was found. The possible difference between these two protocols could be a limiting factor. We aim to determine if the embryos developed in long down-regulated assisted reproductive technology (ART) cycles differ from the ones obtained in antagonist cycles among women matched for age and follicle-stimulating hormone (FSH) administered on cycle day 3. Patients and Methods: Retrospective cohort analysis was done on a population from a university affiliated hospital. 193 women undergoing standard in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) treatment were included. The age and cycle day 3 FSH matched women undergoing either long or short protocols were compared. Group A consisted of women who had long down-regulation with GnRH analogues, group B consisted of women who had used GnRH antagonists. The clinical and ongoing pregnancy rates were compared. Day 3 embryo scores were compared between the groups. Results: Although mean number of aspirated and inseminated oocytes were similar for the groups and average embryo scores were comparable, clinical and ongoing pregnancy rates were higher in group A than in group B. The percentage of embryos with zero fragmentation and 8-10 blastomeres on day 3 was similar in antagonist and long agonist cycles. Conclusion: Long protocol ART cycles will result in comparable percentages of day 3 embryos with symmetric 8-10 blastomeres with zero fragmentation to those in antagonist cycles.
Yaş ve siklusun 3.günü FSH değerleri eşleşmiş kadınlarda uzun ve kısa YÜT lerinde elde edilen embryo kalitesi farklı mıdır?
Keywords: Genel ve Dahili Tıp